(untitled) (University of Khartoum Journal of Agricultural Sciences, 2022)
The effect of three natural waxes (bee, carnauba and jojoba) on quality and shelf-life of ‘Ergon’ tomato cultivar was evaluated. Tomato fruits were harvested at the mature-green stage from a greenhouse belonging to the College of Agricultural Studies, Sudan University of Science and Technology. Fruits were selected for uniformity of size, color and freedom from blemishes and defects, and transported in field boxes to the laboratory. The fruits were washed, treated with 0.1 % sodium hypochlorite (Clorox, 5 %) as a disinfectant and air dried. The waxes were dissolved in olive oil (1:1) and applied by brushing over the surface of the fruits in a thin layer. The treatments were: bee wax, carnauba wax, jojoba wax and untreated (control).They were arranged in a completely randomized design with four replications. The treated and untreated fruits were stored in carton boxes for 30 days at 18±1 ˚C and 80- 85 % relative humidity in a cold room at the Department of Horticulture, Faculty of Agriculture, University of Khartoum. Analysis of variance at significance level of P ≤ 0.05 was performed on the data using SBS (version 23) statistic. The results showed that the natural waxes significantly reduced losses, maintained quality and extended shelf-life of tomato fruits. The wax treatments significantly delayed fruit ripening (6, 4 and 2 days), reduced water loss (34.1, 19.4 and 9.7 %), decreased peel color (40, 20 and 12 %), fruit softening (87.5, 45.0 and 27.5 %), and total soluble solids accumulation (23.2, 13.4 and 7.2 %), in fruits treated with jojoba wax, carnauba wax and bee wax, respectively, compared with un-waxed (control) fruits. Jojoba wax was most effective, followed by carnauba wax and the least was the bee wax. It is recommended that natural waxes, especially jojoba and carnauba waxes, can effectively be used to delay fruit ripening, reduce weight loss, maintain quality and extend shelf-life of tomato fruits.